Characterization of fiber optic sensor for liquid refractive index monitoring - Shafei, Dianay Shafina (2015)
This research was conducted to characterize the fiber optic sensor for liquid refractive index monitoring. The sensor system consists of a light source, a 2x2 single mode fused fiber coupler of different coupling ratios and a detector. Diode laser operating at wavelength 1300 nm and 1550 nm was used as a light source. Fresnel’s Law of reflection from the fiber-air and fiber-liquid interface was the fundamental of this work. The total reflected light intensity from both coupler outputs was measured in terms of its power. A simple test on the feasibility of the sensor for this type of measurement was conducted and it was found that this sensor was sensitive enough and has a reasonable working range to work with. The refractive index of a solution is a function of its concentration, temperature and also the wavelength of the incident light. In this work the relation of these parameters were investigated. The solution of NaCl was selected as a liquid sample. Various concentrations of salt solution ranging from 0 % - 24 % were tested and were heated from 30 ºC - 90 ºC to observe the change in refractive index. The results revealed that the refractive index of liquid solutions varies linearly with its concentration and temperature. Performance of the sensor system by using single mode fused fiber coupler with different coupling ratio was studied. It was observed that the fiber coupler with 50:50 indicated the highest sensitivity to be used in this sensor system.